Pemetaan Polusi Udara Perkotaan di Propinsi Daerah Istimewa Yogyakarta - Agus Tri Basuki; Endah Saptutyningsih (Universitas Islam Indonesia, 2012)
This study aims to identify the areas which have a highest air pollution especially CO and PM1O in province of Yogyakarta Special Region by the Geographical information Systems (GiS) approach.By using Geographical information Systems (GiS) approach, the mapping result shows that highest CO pollution concentrated in Yogyakarta City and Sleman Regency. The areas which have highest CO pollution according to the results of this method are the area located in country of Yogyakarta City, they are Jetis, Gondomanan, Wirobrajan, Kraton, Mantrijeron, sebagian wilayah Ngampilan, Gedongtengen, dan Mergangsan Districts. Some counties of Sleman Regency such as Depok, Ngagiik and Kaiasan Districts have highest CO pollution too.The areas which have PM10 pollutant in province of Yogyakarta Speciai Region are some parts of Yogyakarta City (Mantrijeron, Kraton, Gondomanan, Ngampiian, Gedongtengen, Danurejan, Wirobrajan, Mergangsan, Pakualaman, Jetis, and Gondokusuman Districts) and Gunung Kidul Regency (Karangmojo District)The result of this study can be recommendation for next research to evaluate the areas so that policy maker minimize the negative impacts of air poilution especially for society health.Keywords: Geographical Information Systems (GIS), PM10, CO.